The use of complementary serological and molecular testing for blood-borne pathogens and evaluation of socio-demographic characteristics of intravenous drug users on substitution therapy from Šumadia district of Serbia - Borovčanin, Nemanja; Ristanović, Elizabeta; Todorović, Milena; Borovčanin, Milica; Jovanović, Mirjana; Balint, Bela (Vojnosanitetski pregled, 2021)
Background/Aim. Intravenous drug users (IDUs) are still a high risk-group for cross-reacting blood-borne infections, for vertical pathogen transmission as well as for potentially blood/plasma donation (especially as “paid” donors). The aim of our study was to establish the profile of opiate addict and prevalence of blood-borne pathogens – Hepatitis B virus (HBV), Hepatitis C virus (HCV) and Human Immunodeficiency Virus (HIV) among 99 patients on substitution therapy with methadone and buprenorphine from Šumadia District. Methods. The Treatment Demand Indicator (TDI) of Pompidou-questionnaire was used to assess the history of drug abuse and risk behavior. All blood samples were tested for HBV surface antigen (HBsAg), anti-HCV antibody (anti-HCV) and HIV antigen/antibody (HIV-Ag/Ab) by Enzyme-Linked ImmunoSorbent Assay (ELISA) or Chemiluminescent Immuno-Assay (CIA). Investigations were also performed for HBV, HCV and HIV by molecular testing – Polymerase Chain Reaction (PCR) method. Results. The majority of patients were males (81.8%), median age 32 (19–57) years, lived in a city (99%), unemployed (58.6%), with finished secondary school (67.7%), unsafe injecting practices (34.3%) and never previously tested for HBV (39.4%), HCV (36.4%) nor HIV (28.3%); only 4% of them previously got HBV-vaccine. The complementary testing resulted with following results: HBV ELISA/CIA and PCR negativity for 66 patients and positive results (by ELISA/CIA and PCR) for 19 patients. However, a difference was observed in the ELISA/CIA-negative/PCR-positive result for 12 and ELISA/CIA-positive/PCR-negative for two patients respectively. Further, the negative results for HCV (ELISA/CIA and PCR testing) were found in 15 IDUs and positive results (using both methods) were found in 58 patients. Different results for ELISA/CIA-negative / PCR-positive results were found in 11 IDUs and ELISA/CIA-positive/PCR – negative results were found in 15 patients. All investigated IDUs were negative for HIV (ELISA/CIA and PCR testing) and for pathogens of opportunistic infection (Cryptococcus neoformans; Pneumocystis carinii; PCR testing), as well as for West Nile Virus (PCR testing). Just one IDU was positive for syphilis (ELISA and confirmatory testing). Conclusion. Our study demonstrated that the positivity for HBV and HCV is still very high (33.4% and 84.8%, respectively) in IDUs. Thus, we suggest that drug users have to be periodically screened using a complementary serological/molecular testing – concerning differences/discrepancies in the results obtained using these methods.